Survey on the awareness of government workers towards saving for future / Afifa Nabila Azhar - Azhar, Afifa Nabila (2019)
Saving is one of the essential things that are needed for each of individuals in the future. The aim of this study is to know the awareness of the government workers towards saving for the future and the factors that influence them for savings. This research is questionnaires as a survey method towards government workers in SK Pengkalan Jaya, Tasek Gelugor about the awareness and factors of savings. The findings indicate that all the respondents have the awareness and know how to make savings for the future and majority of them savings in deposit account. It is because they make savings for the emergency use. All of them have the personal allocate for savings for future around 11% and they were influenced by the family to save at the young age. Most of them make savings in the deposit account. Most of the respondents agree that the factors influence them to make savings for better health protection, education spending, financial independence, in case of emergency, to fulfil the luxury of life, high cost of living, to buy future assets and to get comfortable life after retirement.